In Defense of Publics: Projection, Bias, and Cultural Narratives in Science and Religion Debates - Elsdon-Baker, Fern (Zygon, 2019)
John H. Evans's recent book Morals Not Knowledge is a timely argument to recognize broader social and cultural factors that might impact what U.S. religious publics think about the relationship between science and religion and their attitudes toward science and/or religion. While Evans's focus is primarily on what can be classed as moral issues, this response argues that there are other factors that sit within neither the older epistemic conflict model approach nor a moral conflict model approach that also merit further investigation. There is a significant need for further research that examines the social, psychological, (geo)political, and broader cultural factors shaping people's social identities in relation to science and religion debates. When undertaking such research, we need to be wary of creating a binary between scholarly and public space discourse. Social scientific research in this field should be led by public perceptions, attitudes, and views, not by concepts or frameworks that we project onto them.